Dharma Wanita Persatuan di Kecamatan Gatak Kabupaten Sukoharjo - Kuswaji Dwi Priyono (Universitas Muhammadiyah Surakarta, 2010)
This community service activity conducted by lecture and discussion methods in space followed by a documentary film showing the effects of global warming that occurred in various parts of the world. This activity aims to foster understanding of the issue of global warming and reduction efforts to the members of Dharma Wanita Persatuan, Sub District Gatak in Sukoharjo District. After this socialization all members of Dharma Wanita Persatuan Gatak sub-District became aware of the various issues of global warming and efforts to reduce its impact, further reducing the impact of intensified activities in greening the environment with family, school, and their villages.